"But oh, I could it not refine": Lady Hester Pulter's Textual Alchemy - Padaratz, Pricilla (Université d'Ottawa / University of Ottawa, 2016)
Hester Pulter addresses personal and spiritual transformation in a unique way. The elusive nature of alchemical language allows Pulter to express the incomplete, ongoing process of internal transformation, with all its difficulties and inconsistencies. By means of a rich alchemical lexicon, Pulter stresses suffering rather than consolation, conflict rather than reconciliation, and lack of resolution rather than closure in her poetry. She repeatedly tries to see a divine order in earthly suffering, but she insists upon this suffering, and she often argues for a gendered element to this pain, particularly as a mother grieving her dead children. The lack of resolution we see in Pulter's writing pushes against conventional constructions of the ideal female Christian as passively accepting God's plan, and shows the limits of the religious lyric to truly provide consolation. My thesis will extend the discussion of Pulter's use of alchemical imagery and symbols in her poetry, and will argue that she uses alchemical language to reflect how transformation and healing are never, in fact, fully achieved during our physical existence. The promise of literary alchemy as a vehicle for transformation and spiritual regeneration is not always fulfilled in Pulter's work.
Keywords: alchemy; religion; Hester Pulter; women's writing; manuscript; early modern; devotional lyric